Mouse Thalamic Differentiation: Gli-Dependent Pattern and Gli-Independent Prepattern - Haddad-Tóvolli, Roberta; Heide, Michael; Zhou, Xunlei; Blaess, Sandra; Alvarez-Bolado, Gonzalo (Frontiers in Neuroscience, 2012)
Sonic hedgehog (Shh) signaling is essential for thalamic development. The Gli transcription factors act downstream of Shh – while Gli2 is the major activator (GliA), Gli3 acts primarily as a repressor (GliR). The thalamus is remarkable among dorsal structures because of its proximity to the mid-diencephalic organizer, a unique dorsal Shh source. This lends complexity to the interactions between Shh, Gli2, and Gli3, suggesting the presence of a dorsal Gli activator which elsewhere is found only ventrally, and making the dissection of thalamic Gli functions particularly interesting. A current model based on mutant phenotypes in telencephalon and midbrain postulates a degree of reciprocal antagonism of Shh and Gli3 in dorsal brain regions. To approach the role of Gli factors in thalamic specification we first analyzed mice deficient in Gli2 or Gli3. In Gli2 mutants, the thalamus is small and poorly differentiated with the exception of the medial and intralaminar nuclei which, in contrast, are specifically and severely affected by Gli3 inactivation. Gbx2 expression is very reduced in the Gli3 mutant. Most thalamic nuclei are present in both mutants, although incompletely differentiated, as reflected by the loss of specific markers. The ventral posterior group, revealed by novel specific marker Hes1, is present in both mutants and extends axons to the telencephalon. To test the Gli3/Shh interaction we generated a novel mutant deficient in Gli3 and neuroepithelial Shh. The thalamus of the n-Shh/Gli3 double mutants is very large and very poorly differentiated except for a broad domain of Gbx2, Lhx2, and Calb2 expression. In utero electroporation experiments on wild type embryos suggest that a stage-specific factor acting early is responsible for this prepattern. We show that, in the thalamus, GliA acts downstream of Shh to specify pattern and size of the thalamic nuclei to the exception of the medial and intralaminar groups. Gli3A can partially substitute for Gli2A in the Gli2 mutant. GliR is essential for specification and growth of the medial and intralaminar nuclei, contributes to the specification of other thalamic nuclei and reduces thalamic size. GliA (from neuroepithelial Shh signaling) and GliR do not show reciprocal antagonism in the thalamus, and their joint abolition does not rescue the wild type phenotype.